Northern New Spain A Research Guide - Naylor, Thomas H. (University of Arizona Press, 2021)
This research guide was first conceived to fulfill multiple needs of the research team of the Documentary Relations of the Southwest (DRSW) project at the Arizona State Museum. In performing research tasks, it became evident that reference material was scattered throughout scores of books and monographs. A single complete source book was simply not available. Hence, the editors of the DRSW project compiled this guide. The territory under study comprises all of northern Mexico in colonial times.